PEMBUATAN PROTOTYPE GAME EDUKASI BERBASIS ROLE PLAYING GAME (RPG) SEBAGAI MEDIA PEMBELAJARAN KIMIA UNSUR - Andang Wijanarko; Febrian Solikhin (LPPM Universitas Abdurrab, 2022)
Games in the form of learning media are one of the innovations in the world of education. Based on interviews conducted by the author with students and teachers, it was revealed that Chemistry is not one of the materials that are considered difficult. In addition, students are also less interested in taking chemistry lessons because of the difficulty of understanding the material presented. To help and facilitate teachers and students in the learning process of Periodic system of elements in the classroom, making games as a medium for learning Periodic system of elements is an opportunity to be researched. The research method used is ADDIE (Analyze, Design, Development, Implementation, and Evaluation). This research has succeeded in producing educational game products based on role playing games (RPG) as learning media for Periodic system of elements. The educational game was successfully developed using the RPG Maker application. The results of the expert validity test and the teacher's response test to the educational games that were built were 1) Material expert validators with an average value of 3.33 were in the very good category 2) Media expert validators with an average value of 3.22 were in the good category 3) The learning expert validator with an average value of 3.27 is in the very good category. 3) The results of the teacher's response test with an average value of 3.62 are in the very good category. The results of the validity test and response test showed that the educational game made was feasible to be implemented in the classroom and used as a learning medium for Periodic system of elements.